Analysis of Student Ethics in the Classroom Learning Process at SDN X Minangkabau - Safrizal Safrizal; Radika Radika; Elis Komalasari; Le Liam (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
This research is motivated by circumstances where researchers see the phenomenon of a lack of student ethics during the learning process in class X Minangkabau Elementary School. The purpose of this study is to describe how the teacher's strategy in improving ethics during the learning process in class SD X Minangkabau. In this study using qualitative research methods. The informants of this study were 1 grade V elementary school teacher, 20 grade V students selected by purposive sampling. The instrument in this study was the researcher himself, with data collection techniques and the researcher was assisted by supporting instruments in the form of observation guidelines, interview guidelines and documentation studies. The data analysis technique uses the data reduction, data display and conclusion stages. Guarantee the validity of the data in this study using triagulation by combining 3 ways of data collection. The results of this study indicate that the strategy used by the teacher in improving student ethics during the learning process in class is by linking the PPKN material learned with everyday life, linking the BAM material studied with everyday life, linking the Ecosystem material studied with everyday life -day and using learning media.